2018
DOI: 10.3390/ijms19113540
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Proliferator-Activated Receptors (PPAR)γ Agonists as Master Modulators of Tumor Tissue

Abstract: In most clinical trials, thiazolidinediones do not show any relevant anti-cancer activity when used as mono-therapy. Clinical inefficacy contrasts ambiguous pre-clinical data either favoring anti-tumor activity or tumor promotion. However, if thiazolidinediones are combined with additional regulatory active drugs, so-called ‘master modulators’ of tumors, i.e., transcriptional modulators, metronomic low-dose chemotherapy, epigenetically modifying agents, protein binding pro-anakoinotic drugs, such as COX-2 inhi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 127 publications
0
62
0
Order By: Relevance
“…PPAR-γ plays an important role in maintaining energy homeostasis through the modulation of glucose and lipid metabolism, and PPAR-γ is usually overexpressed in cancer cells causing accelerated tumor growth [58,59]. However, the role of PPAR-γ agonists and antagonists in tumor treatment is complex, as both have been found to inhibit the growth of tumor cells [58,[60][61][62]. PPAR-γ has been found to promote glucose uptake during lipid metabolism, and can induce the expression of glycolytic proteins, including GLUT-4 [63].…”
Section: Discussionmentioning
confidence: 99%
“…PPAR-γ plays an important role in maintaining energy homeostasis through the modulation of glucose and lipid metabolism, and PPAR-γ is usually overexpressed in cancer cells causing accelerated tumor growth [58,59]. However, the role of PPAR-γ agonists and antagonists in tumor treatment is complex, as both have been found to inhibit the growth of tumor cells [58,[60][61][62]. PPAR-γ has been found to promote glucose uptake during lipid metabolism, and can induce the expression of glycolytic proteins, including GLUT-4 [63].…”
Section: Discussionmentioning
confidence: 99%
“…Glitazones are the most frequently used transcriptionally active master modulators for anakoinosis induction besides glucocorticoids (Heudobler et al, 2018b ). For example, pioglitazone, a peroxisome-proliferator-activated receptor (PPAR) γ/α agonist, seems to be an important many-sided applicable master modulator for communicative processes in neoplasia.…”
Section: Specific Methodsological Aspects Of Anakoinosis Inducing Thermentioning
confidence: 99%
“…However, it was first reported that GW501516, a PPARβ/δ agonist, protected mice on a HFD from obesity by activating the lipin1-PGC1α-PPARα pathway, thus increasing fatty acid intake and oxidation [74]. In addition, given the high expression of PPARβ/δ in the intestine, HFD- and agonist-activating PPARβ/δ promoted organoid to product progenitors and even facilitated tumor formation in vivo to inhibit the tumor suppressor adenomatous polyposis coli (APC) protein [75,76]. For mice fed a HFD, the expression of PPARs depended on many factors, including species and tissue type and period of development.…”
Section: Action Of Ppars In Nutrient Metabolismmentioning
confidence: 99%